What drives euro area break-even inflation rates? - Matteo Ciccarelli; Juan Angel García (European Central Bank (ECB), 2009)
The yield spread between nominal and inflation-linked bonds (or break-even inflation rates, BEIR) is a fundamental indicator of inflation expectations (and associated premia). This paper investigates which macroeconomic and financial variables explain BEIRs. We evaluate a large number of potential explanatory variables through Bayesian model selection techniques and document their explanatory power at different horizons. At short horizons, actual inflation dynamics is the main determinant of BEIRs. At long horizons, financial variables (i.e. term spread, bond market volatility) become increasingly relevant, but confidence and cyclical indicators remain important.
Keywords: C11; C52; E31; 330; Bayesian model selection; break-even inflation rates; business cycle indicators; inflation risk premia; Zinsstruktur; Risikoprämie; Inflationserwartung; Wirtschaftsindikator; Bayes-Statistik; Eurozone